Cardiac Remodeling: Concepts, Clinical Impact, Pathophysiological Mechanisms and Pharmacologic Treatment - Azevedo, Paula S. [UNESP]; Polegato, Bertha F. [UNESP]; Minicucci, Marcos F. [UNESP]; Paiva, Sergio A R [UNESP]; Zornoff, Leonardo A M [UNESP] (My University, 2016)
Cardiac remodeling is defined as a group of molecular, cellular and interstitial changes that manifest clinically as changes in size, mass, geometry and function of the heart after injury. The process results in poor prognosis because of its association with ventricular dysfunction and malignant arrhythmias. Here, we discuss the concepts and clinical implications of cardiac remodeling, and the pathophysiological role of different factors, including cell death, energy metabolism, oxidative stress, inflammation, collagen, contractile proteins, calcium transport, geometry and neurohormonal activation. Finally, the article describes the pharmacological treatment of cardiac remodeling, which can be divided into three different stages of strategies: consolidated, promising and potential strategies.